Sistem Keseimbangan Segway Menggunakan Kontrol Proportional Integral dan Derivatif (PID) - Made Rahmawaty; Thalia Smart Aritonang; Tianur; Wiwin Styorini; Muhammad Diono (Jurnal Elektro dan Mesin Terapan, 2022)
Segway is a mobile robot that has two wheels on the right and left that will not be balanced if there is no controller. The Proportional Integral Derivative (PID) control is used to determine the magnitude and speed of the DC motor rotating as a driving force, so that the balancing tool can maintain its position perpendicular to the surface of the earth on a flat surface. This tool is controlled by using a microcontroller-based controller using Arduino, so that the robot's motion system becomes automatic in accordance with the program created by the controller. Segway uses the MPU 6050 sensor module as a sensor in which there is a gyroscope and accelerometer as well as making it easier to detect a speed and acceleration angle as input to the Segway. The resulting data will be processed in Arduino so that the DC motor will actively balance the Segway. Segways have a maximum angle of 10 ° to get back to the point of 0 °. Segway can be balanced with PID parameter values that are close to optimal are Kp = 3.55, Ki = 0.005, Kd-2.05 by having a fast settling time at the 0.71 second